Clinical and laboratory characteristics of mycobacteriosis in persons with HIV and case report of severe generalized mycobacteriosis - O. E. Pobegalova; N. S. Zhevnerova; K. E. Vinogradova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Relevance. In the context of HIV epidemic, the number of cases of mycobacteriosis has increased.The objective was to study clinical and laboratory characteristics of mycobacteriosis in HIV patients; to present a clinical case of severe generalized mycobacteriosis.Methods and materials. Retrospective analysis of 48 cases from the archives of the St. Petersburg State Budgetary Healthcare Institution «S. P. Botkin Clinical Infectious Diseases Hospital» over the period from 2016 to 2018 was performed. The inclusion criterion was newly diagnosed mycobacteriosis. The following parameters were evaluated: HIV infection duration and stage; antiretroviral therapy (ART) duration; the primary syndrome and form of mycobacteriosis; laboratory and instrumental findings; causative pathogen verification methods.Results. Median number of CD4-lymphocytes (CD4 + ) was 6.9 cell/pl. In 33.3 % of patients, HIV infection was diagnosed within 1 year before the detection of mycobacteriosis. The primary syndromes were: febrile-toxic syndrome (72.9 %), bronchopulmonary syndrome (29.2 %), diarrhea syndrome (18.8 %), abdominal pain syndrome (10.4 %). Generalized myco-bacteriosis was diagnosed in 65.3 % patients. Anemia was registered in in 96 % patients, leukopenia — in 43.8 % patients. Lymphadenopathy of various localization was the most common instrumental finding (75 %). The diagnosis was confirmed bacteriologically in 70.8 % cases. Mycobacterium avium complex group was predominant (62.5 %). There were 18.8 % deaths.Conclusion. Mycobacteriosis developed in patients with advanced immunodeficiency. Clinical and laboratory findings were nonspecific. There was a trend towards generalization of infection. The proportion of deaths indicates the high importance of mycobacteriosis in the structure of mortality in HIV patients.